Culture. Science. Education: modern trends - Vinokurov A. A., Nabokova L. S., Khalina N. V., Anikin D. V., Valiulina E. V., Dorokhov N. I., Stepanova T. I., Tselishcheva Z. A., Kuznetsova E. V., Bezgodov A. V., Kurasova E. A., Kurasova E. A., Stenkina E. N., Savitskaya E. V., Kostenko E. G., Lysenko V. V., Saikina G. K., Kadnikova O. I., Altynbaeva G. K., Aidarkhanov A. M., Toretaev M. O., Valiulin R. R., Valiulina E. V., Sukhomlina T. A., Kasianenko T. G., Vorotilkina A. M., Sergeev T. S., Alisin V. V., Svinukhov V. G., Senotrusova S. V., Zhoglicheva V. V., Tesalovskaia V. E., Sovetova N. P., Aksiutina S. V., Dosbenbetova A. S., Abramova G. I., Iumasheva E. V., Stashkov V. B., Anishchenko N. D., Pospelov A. A., Rozanov K. I., Kolovanov O. A., Dylevskaia L. A., Sovetova N. P., Chaika N. M., Pavliuk T. P. (Culture. Science. Education: modern trends, 2020)
The article is devoted to the consideration of the role of Nikita Yakovlevich Bichurin (O. Iakinf), a native of Chuvashia (1777–1853), a graduate of the Kazan theological Academy, a head of the ninth Russian spiritual mission in China (1807–1821), a corresponding member of the Russian Academy of Sciences (1828), an author of many dictionaries and scientific works on sinology, the owner of four Demidov prizes, a founder of Russian Oriental studies, who left a deep trace in the science and culture of Russia and Chuvashia. In commemoration of the scientist monuments were erected, localities and streets as well as state and public awards are named after the scientist and etc. The history of the Bichurin prize, established by the government of the Chuvash Republic for achievements in the field of science, is described. The first winner of this award was a creative team of four persons: N.G. Grigoriev, V.B. Lyubovtsev, S.G. Khisin, Y.V. Denisov. The article informed us about the essence of the development of this scientific community conveyor technology for mass examination and treatment of patients by reflexology methods. The role of each winner in the overall innovative product is revealed. The question is raised about the need to restore the interrupted tradition of awarding this government award.
Keywords: Китай; просветительство; enlightenment; миссионерство; Denisov; China; Бичурин Н; научное востоковедение; премия имени Н; Бичурина; рефлексотерапия; Григорьев Н; Любовцев В; Хисин С; Денисов Ю; missionary work; scientific oriental studies; Bichurin prize; reflexology; Bichurin; Grigoriev; Lyubovtsev; Khisin